Learning Journals : A handbook for reflective practice and professional development - Moon, Jennifer A. (London : Routledge, 2006)
Jennifer A. Moon offers guidance on keeping and using journals and gives step-by-step advice on integrating journal writing on taught courses and in training and professional development.
Previous ed.: 1999.
Formerly CIP.
Includes bibliographical references (p. [182]-196) and index.
Keywords: Learning; Diaries -- Authorship -- Study and teaching